2018
DOI: 10.1002/smll.201704491
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Additive‐/Post‐Treatment‐Free Nonfullerene Polymer Solar Cells via Tuning Molecular Weight of Conjugated Polymers

Abstract: In recent years, rapid advances are achieved in polymer solar cells (PSCs) using nonfullerene small molecular acceptors. However, no research disclosing the influence of molecular weight (M ) of conjugated polymer on the nonfullerene device performance is reported. In this work, a series of polymers with different M s are synthesized to systematically investigate the connection between M and performance of nonfullerene devices for the first time. It is found that the device performance improves substantially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…It has been recognized as a great promising substitute for silicon‐based photovoltaic with advantages of light weight, inexpensive cost, and large‐area flexible preparation with roll‐to‐roll (R2R) process. Besides understanding the internal mechanism of binary OSCs deeply, more and more efforts were paid to improve the performance of OSCs via tuning absorption and energy level of novel donor and acceptor materials, optimizing processing methods, interfacial engineering, and innovative device architectures …”
Section: Introductionmentioning
confidence: 99%
“…It has been recognized as a great promising substitute for silicon‐based photovoltaic with advantages of light weight, inexpensive cost, and large‐area flexible preparation with roll‐to‐roll (R2R) process. Besides understanding the internal mechanism of binary OSCs deeply, more and more efforts were paid to improve the performance of OSCs via tuning absorption and energy level of novel donor and acceptor materials, optimizing processing methods, interfacial engineering, and innovative device architectures …”
Section: Introductionmentioning
confidence: 99%
“…By comparing the device performance parameters, it is found that the V OC value slightly increases from 720 mV (J51-8kDa) to 753 mV (J51-36kDa), while the J SC and FF prominently increase from 5.42 to 12.18 mA cm À2 and 39.89% to 65.06%, respectively, because of the higher molar mass fractions, the higher charge mobility. 40,41 The surface morphology of optimal J51:PC 71 BM blends on ZnO-coated ITO was examined via atomic force microscopy (AFM) and measured in tapping mode (as shown in Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23][24] Molecular weight is one of the most important parameter for polymer donors because molecular weight directly inuences optical-electricity property, solubility and the morphology of the active layer. [25][26][27][28][29][30][31] Relatively little efforts have been made to reveal how polymer molecular weight affects the device performance in OSCs, as it is difficult to control the polymer molecular weight well during the synthesis. With the increase of PBTIBDTT-S' M n from 12 to 38 kDa, the PCEs of PBTIBDTT-S:PC 71 BM devices gradually increased due to the large improvement in J sc and slight enhancement in FF.…”
Section: Introductionmentioning
confidence: 99%
“…This is different from the trend observed from fullerene‐based solar cells. The distinct molecular weight effects of polymer donors for different acceptors demonstrated in this paper will benefit the understanding of structure–property relationship and further development of new conjugated polymers for high efficiency PSCs 12b,30…”
Section: Figurementioning
confidence: 91%